The problems of infrageneric classification of Eulophia R. Br. ex Lindl. (Orchidaceae, Cymbidiinae) - Cieślicka, Dorota (Biodiversity: Research and Conservation, 2006)
The genus Eulophia comprises about 230 species. It has a wide distribution range - from tropical and subtropical Africa and Madagascar, through Asia to Australia; one species occures also in tropical America. For 723 records found for Eulophia in the International Plant Name Index, more than 500 are probably synonyms. Infrageneric classification of the genus is also complicated by the morphological diversity. We have to deal with situation where problematic species, not matching terms of smaller and well defined allied genera, are arbitrarily included into Eulophia. Proposed infrageneric classification will be based upon methods of classical taxonomy, particularly examination of generative and vegetative characters. Additionally, the results of examination will be compared with data obtained from molecular studies and scanning electron microscopy (SEM). Phylogenetic analysis will utilize nucleotide variation among sequences of selected DNA markers, preferably Internal Transcribed Spacer of nrDNA multigene family. Those will be followed by biogeographic analysis with focus on methods of phylogenetic biogeography. Precise study of genus Eulophia is essential to access the limits of many species and to propose sectional arrangements for the entire range.